2009
DOI: 10.1111/j.1600-0501.2008.01638.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized split‐mouth study comparing iliac onlay grafts in atrophied edentulous patients: covered with periosteum or a bioresorbable membrane

Abstract: This study provides evidence that after avascular iliac bone grafting, the revascularization of the graft was sufficient after 3 months regardless of the graft coverage with no effect on the amount of initial resorption of the graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 53 publications
(78 reference statements)
2
51
1
1
Order By: Relevance
“…A lower percentage of 1.3% (6/436) of additional augmentation procedures at the time of implant placement was found in the present study and was not considered as primary complication [69]. The authors attributed the low graft resorption to the short healing period of 3 to 5 months, which has now proven to be sufficient for the revascularization of the graft and the secure insertion of dental implants as suggested in the past by various authors [70, 71]. Therefore, we suggest limiting the healing period after autologous bone grafting to a maximum of 3 to 6 months.…”
Section: Discussionsupporting
confidence: 58%
“…A lower percentage of 1.3% (6/436) of additional augmentation procedures at the time of implant placement was found in the present study and was not considered as primary complication [69]. The authors attributed the low graft resorption to the short healing period of 3 to 5 months, which has now proven to be sufficient for the revascularization of the graft and the secure insertion of dental implants as suggested in the past by various authors [70, 71]. Therefore, we suggest limiting the healing period after autologous bone grafting to a maximum of 3 to 6 months.…”
Section: Discussionsupporting
confidence: 58%
“…Proliferation of the cells varied slightly between the individuals, but the proliferation rate of the aHOBs was significantly higher than the proliferation rate of the iHOBs. Interindividual differences in the number of cells has been described previously in bone marrow stromal cells (BMSC) from the alveolar bone and can be correlated to the interindividual differences found in the rate of new bone formation in oral bone healing and bone transplants in vivo (Heberer et al, 2009;Marolt et al, 2014). Matsubara et al (2005) also reported a difference in the proliferation behavior of BMSCs derived from the alveolar bone compared with BMSCs from the ilium in dogs.…”
Section: Discussionmentioning
confidence: 66%
“…Thus, both implant success and the extent of horizontal dimension gain should be clearly reported. In this study, the primary outcome was the mean gain in ridge width, and measurements were performed 6 mm apical to the crest, immediately above the head of the fixation screw, analogous to the method used by Heberer and colleagues . This modification of the traditional positioning prevents malposition of the caliper, ensures reproducibility during reentry, and provides a more accurate positioning for posterior radiographic measurements …”
Section: Discussionmentioning
confidence: 99%
“…In this study, the primary outcome was the mean gain in ridge width, and measurements were performed 6 mm apical to the crest, immediately above the head of the fixation screw, analogous to the method used by Heberer and colleagues. 78 This modification of the traditional positioning prevents malposition of the caliper, 46,48,79,80 ensures reproducibility during reentry, and provides a more accurate positioning for posterior radiographic measurements. 79 The mean horizontal bone gain of 3.63 1 1.28 mm presented in this study, ranging from 1 to 7 mm, is similar or superior to those presented in studies that use the same methodology for measurement.…”
Section: Discussionmentioning
confidence: 99%